Fracture mechanics study on 3-D interacting edge cracks in offshore pipelines - Ashley Ivana John (Nanyang Technological University, 2023)
Pipelines are a critical transportation infrastructure that plays a vital role in the safe and efficient delivery of natural gas, crude oil, and other liquids from production sites to consumption centres. Under particular conditions, the failure of offshore oil and gas pipelines occurs as a result of some mechanical forces applying pressure. These circumstances pose a possible risk to the pipelines' integrity and in-service life, which could result in resource loss and environmental damage. According to several studies, pipeline failure can be attributed to weld failure, fatigue crack growth, corrosion fatigue, stress corrosion cracking, and fluid flow-induced erosion. The objective of this report is to study the fracture mechanics on 3D interacting edge cracks in offshore pipelines. For analysing various crack interactions, a Finite Element (FE) technique was used. Furthermore, the FE model was applied to study the non-uniform stress distribution generated by the interaction impact between cracks. The interaction of numerous cracks was modelled using a Finite Element (FE) approach. The FE model was used as well to study the non-uniform stress distribution that results from the interaction impact between cracks.